Geochemical characteristics of hydrogen, oxygen, carbon isotopes and REE of cenozoic dolomites in Well Xike 1, Xisha Islands, South China sea and the significance for dolomitization in island-reef areas - Li, Xiaoyu; Shi, Zhiqiang; Han, Lu; Hu, Xiaolong (Frontiers in Earth Science, 2023)
Due to the special tectonic background and complex geological evolution characteristics of the South China Sea, reef dolomite reservoirs (sush as Well Xike) are widely developed. Based on the drilling core data of Well Xike 1, the structure and geochemical characteristics of dolomite reservoirs, including carbon, oxygen, hydrogen isotopes and REE were systematically studied, using geochemical and petrological methods. It is found that the geochemical characteristics of REE show that the main diagenetic environment of dolomite is low-temperature alkaline semi open oxidation environment; the carbon and oxygen isotopes of the dolomite are generally lack of correlation, δD is significantly lower than the hydrogen isotope value of seawater. Meanwhile, the oxygen isotope value of deep dolomites is negatively biased, which may be due to the increase or decrease of pore water temperature caused by deep thermal convection that related to the regional tectonic movements of the South China Sea. The δ18O value is also consistent with the geological reality of increasing saddle dolomite content in deep dolomites. The distribution of δ13C value indicates that the dolomite inherited the carbon of the original limestone during dolomitization, while the characteristic of δD value shows that it may be affected by the mixing of atmospheric precipitation and concentrated seawater in the quasi contemporaneous period. Based on the comprehensive analysis of the geochemical characteristics of the Well Xike 1, it is considered that the higher diagenetic temperature could be an important factor leading to the huge differences between the diagenetic model of deep and shallow dolomites. The geochemical characteristics of the shallow dolomites show that it is mainly reflux infiltration dolomitization under the micro evaporation and concentration sea water environments, while the deep dolomite is transformed by the hot water fluids in the epigenetic diagenetic evolution stage.